1988
DOI: 10.1097/00004032-198812000-00008
|View full text |Cite
|
Sign up to set email alerts
|

BIOKINETICS AND DOSIMETRY OF INHALED Cm AEROSOLS IN BEAGLES: EFFECT OF AEROSOL CHEMICAL FORM

Abstract: A rapid, sensitive and highly selective technique using Delayed Neutron Activation Analysis (DNAA) has been used to determine U concentrations in human tissues. Two different sample preparation techniques were compared: one involves total matrix destruction to a dry ash while the other is a nondestructive preparation of the wet sample. The data obtained from the analyses of the same sample by DNAA of wet tissues, DNAA of ashed tissues and from radiochemical analyses using alpha spectroscopy (a standard method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
2
9
2
Order By: Relevance
“…This assumption inflates the calculated soluble fraction because some rephagocytosis may occur with the remaining viable cells. Therefore, we concluded that the apparent differences between the results ofthe previous in vivo study (12) and those of the present study were not as significant as they first seemed.…”
Section: Dissolution Of 2"cm203 In Alveolar Macrophagescontrasting
confidence: 68%
See 2 more Smart Citations
“…This assumption inflates the calculated soluble fraction because some rephagocytosis may occur with the remaining viable cells. Therefore, we concluded that the apparent differences between the results ofthe previous in vivo study (12) and those of the present study were not as significant as they first seemed.…”
Section: Dissolution Of 2"cm203 In Alveolar Macrophagescontrasting
confidence: 68%
“…Figure 2 shows the results ofthis analysis along with the original dissolution curve. This analysis demonstrates that approximately 45 % dissolved in 7 days, a result that is not in close agreement with the in vivo data (12).…”
Section: Dissolution Of 2"cm203 In Alveolar Macrophagescontrasting
confidence: 59%
See 1 more Smart Citation
“…Most of the curium was absorbed rapidly. Analysis here of both the oxide and chloride data gave s r = 0.4 d −1 . (493) Guilmette and Kanapilly (1988) studied the tissue distribution of 244 Cm in dogs for 2 y after inhalation of 244 Cm 2 O 3 and 244 Cm(NO 3 ) 3 , and observed broadly similar kinetics. Analysis here of the oxide and nitrate data gave s r = 0.1 and 0.5 d −1 , respectively. (494) Seven studies were carried out in rats, involving inhalation of the citrate, nitrate, or oxide; estimated values of s r ranged from 0.15 to 10 d −1 . (495) The results of analyses here are summarised in Table 24.6; values of s r range from 0.1 to 10 d −1 with a median of 0.4 d −1 .…”
Section: A Generic Biokinetic Modelling Scheme For the Actinidesmentioning
confidence: 85%
“…Instrumental neutron activation analysis (NAA) involves excitation of U nuclei in a sample, then measuring the radiation emitted from the excited nuclei (Gladney ef a/ 1976(Gladney ef a/ , 1978(Gladney ef a/ , 1980Gonzales et a/, 1988). 238U and 235U produce radiation of characteristic energies that are proportional to the amount of each isotope in a sample.…”
Section: Existing Ermmentioning
confidence: 99%